Internet e jurisdição entre poderes estatais e corporativos: o caso do direito ao esquecimento - Lahis Pasquali Kurtz (2022)
This research reflected on the effects of the application of the right to be forgotten on the internet, characterized as protection of data protection implemented by local jurisdictions, and carried out by global search engines. The agenda is guided differently by government agents, such as the European Union, and corporate agents, such as search engines. This situation implies reflexes for the legal system, which can be observed in the Brazilian context. The problem investigated is: the discourse of protection of free expression and information, managed by multinational search engines to face demands for the right to be forgotten in the European Union, potentiates the risk of collateral censorship in its application in jurisdictions affected by this regulatory debate, such as Brazil? The goal was to verify the effects of the protection of the right to be forgotten on the three fundamental rights ruled on its application: the protection of personal data, with a focus on informational self-determination, freedom of expression and access to information. For this, the methodology adopted was the study of the regulation of the right to be forgotten from three perspectives: 1) the socio-legal theory on privacy and data protection, in order to understand how the internet provides a unique way of interlocution of data protection with the access to information and freedom of expression, as well as identifying conceptual, legal and sociological points that are still unexplored or insufficient in the specialized literature on the subject; 2) the Google Spain case, which represents the framework for the conception of a right to be forgotten as an autonomous category and mobilizes the international debate on the subject, as well as its consequences on the role of online information intermediaries and their relationship with the public sphere, with content analysis of the 7 meetings of Google's Advisory Board on the decision; 3) the normative production, in the jurisprudence and in the legislation, such as Case Google vs. CNIL and Case C-136/17 from European Union, that aims to answer demands on an effective protection of personal data in the face of the new possibilities of loss of control created by the internet. The hypothesis that the right to be forgotten would present greater risks to free expression and access to information in Brazil if transposed to our system from the protection implemented in the European Union, proved to be insufficient. The results denote multiple concepts for the terminology right to be forgotten. The one applied to search engines and formally regulated is not based on reputation, but on data protection, although there are remnants of this concept in its legal framework. The antagonism between data protection and informational rights is raised in a context of identification between these rights and the goods and services offered by intermediaries on the internet. In this context, while there may be a risk in the transposition of the right to be forgotten in Brazil due to the expansion of data protection as a legal category, due to the lack of inspection mechanisms on the agents that will implement it, there is also risk in the importation of criticisms of this regulation, through an argument that subverts informational self-determination into a threat to access to information.